Generasi Z sebagai Agen Perubahan: Upaya Mencapai Harmoni di Tengah Multikulturalisme - Ramadani, Safira Laila (Maliki Interdisciplinary Journal, 2026)
Generation Z (Gen Z), defined as those born between 1995 and 2010, are characterized as "digital natives" due to their growth coinciding with the rapid acceleration of information technology. This unique feature distinguishes Gen Z from previous generations, with internet access and digital devices being a fundamental aspect of their daily routines.This research aims to analyze the significance of Generation Z's contribution to creating and maintaining harmony amidst the complexity of social diversity. The main focus of this study is to identify the specific roles that Gen Z can assume to realize harmony within diversity. Based on the literature review method, the research findings point to three key initiatives that Gen Z can implement to strengthen societal cohesion: first, fostering National Solidarity; second, utilizing Social Media for education and unity campaigns; and third, organizing Inter-Religious Dialogue. Broadly speaking, the study's findings underscore the vital role of Generation Z in preserving the peace of Indonesia's pluralistic society. As digital natives, they possess the capacity to disseminate the values of tolerance and inclusivity through various channels, including social media platforms, social activism, cross-cultural exchange, and political education. Although they face challenges, Generation Z holds immense potential to become a transformative force in strengthening solidarity and rebuilding trust among various cultural groups.